The Hierarchical Rater Thresholds Model for Multiple Raters and Multiple Items - Molenaar Dylan; Uluman Müge; Tavşancıl Ezel; De Boeck Paul (De Gruyter, 2021)
In educational measurement, various methods have been proposed to infer student proficiency from the ratings of multiple items (e.g., essays) by multiple raters. However, suitable models quickly become numerically demanding or even unfeasible as separate latent variables are needed to account for local dependencies between the ratings of the same response. Therefore, in the present paper we derive a flexible approach based on Thurstone's law of categorical judgment. The advantage of this approach is that it can be fit using weighted least squares estimation which is computationally less demanding as compared to most of the previous approaches in the case of an increasing number of latent variables. In addition, the new approach can be applied using existing latent variable modeling software. We illustrate the model on a real dataset from the Trends in International Mathematics and Science Study (TIMMSS) comprising ratings of 10 items by 4 raters for 150 subjects. In addition, we compare the new model to existing models including the facet model, the hierarchical rater model, and the hierarchical rater latent class model.